2010
DOI: 10.1007/s10682-010-9390-5
|View full text |Cite
|
Sign up to set email alerts
|

How internode length, position and presence of leaves affect survival and growth of Alternanthera philoxeroides after fragmentation?

Abstract: Disturbance is common in nature and disturbance-caused fragmentation of clones happens frequently in stoloniferous plants. After fragmentation storage in stolon internodes and leaves may enhance survival and growth of stoloniferous plants. We hypothesize that (1) increasing length of the internode attached to the ramet and (2) presence of leaves will increase ramet survival and growth, and that (3) internode positions (before or after the ramet or both) will also play a role. We tested these hypotheses with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
95
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 37 publications
7
95
1
Order By: Relevance
“…40% greater than that from stem sections with one node (Song et al 2013). This suggests that longer stem sections with more than one node may contain more stored reserves than shorter ones (Suzuki and Stuefer 1999, Dong et al 2010a, Dong et al 2010b, Song et al 2013. The higher survival rate of M. micrantha stem sections with more than one node in our study is in general agreement with other studies undertaken on other vegetatively reproductive species such as S. (Stuefer and Huber 1999), peak downs curse (Polymeria longifolia Lindl.)…”
Section: Discussionsupporting
confidence: 92%
“…40% greater than that from stem sections with one node (Song et al 2013). This suggests that longer stem sections with more than one node may contain more stored reserves than shorter ones (Suzuki and Stuefer 1999, Dong et al 2010a, Dong et al 2010b, Song et al 2013. The higher survival rate of M. micrantha stem sections with more than one node in our study is in general agreement with other studies undertaken on other vegetatively reproductive species such as S. (Stuefer and Huber 1999), peak downs curse (Polymeria longifolia Lindl.)…”
Section: Discussionsupporting
confidence: 92%
“…The growth (in terms of number of new ramets and mean biomass per plant) of floating plants with large stem bases was greater than of plants with small stem bases. Dong et al (2010) also found that the survival and growth of ramets of the invasive plant Alternanthera philoxeroides increased with the length of connected stolons after fragmentation. Although we did not measure the mobilization of carbohydrates and nitrogen in E. crassipes, we found that the stem bases were dramatically depleted, especially large stem bases.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, organic reserves in plant tissue are critical for winter stress tolerance and rapid regrowth (Volenec et al 1996). Storage organs, such as stolons and stem bases, can store soluble carbohydrates and proteins that can be retranslocated among inter connected ramets to improve the survival and growth of clonal plants under natural disturbances and environmental stresses (Madsen et al 1993, Stuefer & Huber 1999, Dong et al 2010. Therefore, greater stored resources contained in larger storage organs can be retranslocated to attached ramets and may facilitate the biomass accumulation and production of new ramets (Danckwerts & Gordon 1989, Baur-Höch et al 1990, Stuefer & Huber 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the survival and growth of small clonal fragments have contrasted the probability of establishment of seeds and fragments of the same species (e.g., Going et al 2008) and found effects of such environmental factors as substratum, burial, and the orientation at which fragments lodge (Bimova et al 2003;Di Carlo et al 2005;Dong et al 2010a;Xie et al 2010). Although size of fragments is an obvious and likely factor, relatively few studies have explicitly tested its effects on survival or growth, and those that have reported different effects in different species (Cabaço et al 2005;Truscott et al 2006;Klimešová et al 2008).…”
Section: Introductionmentioning
confidence: 99%